Carcinoid lung: diffuse pulmonary infiltration by a multifocal bronchial carcinoid. Issue 2 (April 1976) - Skinner, C; Ewen, S W
Abstract : A 20-year-old student presented with diarrhoea and miliary mottling in the chest radiograph. Biopsy specimens of lung and cervical lymph node showed diffuse multifocal carcinoid tumour. No deterioration in clinical state, radiographic appearances or lung function has occurred after two years' treatment with melphalan.